NERAPAN MODEL SHARED DALAM PEMBELAJARAN UNTUK MENINGKATKAN KEMAMPUAN SISWA - Siti Robiah; Rosa Linda Tampubolon; Putri Nurmalasari; Yulia Elfrida Yanti Siregar (STKIP Subang, 2024)
Integrated learning is a model learning that combines several different subjects or areas of learning to provide meaningful experiences to students, by looking at the same concepts, attitudes, and skills that are interconnected with each other. The shared learning model is usually applied in the learning process of disciplines such as mathematics and natural sciences. In implementing this model of integrated learning, the role of collaboration between teachers is needed, teachers need to do careful planning by selecting concepts from several subjects in learning, skills and attitudes that are interrelated into one learning presentation. The implementation of integrated learning in elementary schools is an effort to improve the quality of education and provide meaningful learning experiences to students in everyday life.